Challenging Space and Time: Popular Theatregoing and the Anxieties of Modernity. Issue 1 (1st June 2014) - Emeljanow, Victor
<x xml:space="preserve">Abstract</x> This article raises some questions and issues about the ways in which popular theatregoing was affected in the period 1880– 1914 by changes in work and leisure habits brought about by the technological advances of modernity. Among these changes the most significant, of course, was the advent of the cinema. Did the medium create a new audience or did it wean away the existing theatre spectators, perhaps disaffected by the escalating costs of theatregoing or the erosion of a sense of identification between space and spectator? The question of identity is central to any such discussion: it is the search for identity and value which preoccupied theatre and cinema managers and equally the audiences they hoped to attract in the period to World War 1.